Chapter 2 Epidemics and subaltern classes - Tomasello, Federico (Taylor & Francis, 2024)
This chapter addresses the interpretations of the emerging social question in the field of post-revolutionary French liberalism. It focuses on the cholera outbreak of 1832 to describe how it fostered unprecedented and dramatic representations of urban pauperism chiefly marked by feelings of panic and distress with respect to the new "dangerous classes" brought into being by the Industrial Revolution. By analysing the pandemic crisis, the chapter shows that these subjects were initially perceived not merely as a different social class, but also - and especially - as a different "race," according to a conception exemplified by the metaphor of "new barbarians" invading the manufacturing cities. Hence, the chapter retraces a transformation whereby these initial representations of the subaltern classes based on fear and exclusion gradually gave way to the rise of social research on the subaltern classes aimed at elaborating new welfare policies as risk reduction strategies. These initiatives of social investigation are described as marking the origins of the methods and epistemology of modern social sciences, which are the focus of the following chapter.